Solid-state polymer composite electrolyte, method for preparing the same, and solid-state battery
Patent Information
- Application Number
- CN202611146905.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
但在固态复合电解质体系中,填料颗粒往往难以均匀分散,易发生团聚,导致局部电流分布不均,进而引发界面处锂离子沉积不均匀的问题
[0019]与现有技术相比,本发明提供一种高强度、良好界面相容性的固态聚合物复合电解质,包括:具有离子传导惰性的刚性高分子纤维基底,以及通过前驱体溶液浇注形成在该基底上的复合电解质层;所述前驱体溶液包含电解质盐、聚环氧乙烷和路易斯酸,所述路易斯酸为有机铜盐。本发明实施例主要采用功能化分区策略设计电解质结构,其中无规分布的高分子纤维骨架作为刚性区,可抑制锂枝晶生长,路易斯酸通过静电相互作用、减少离子传输区的结晶区来提升离子电导率。所述的复合电解质具有极大提升的综合性能,能够平衡在电池内部对于固态电解质界面相容性与机械性能难以兼得的问题或需求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and specifically relates to a solid polymer composite electrolyte, its preparation method, and a solid battery. Background Technology
[0002] As a battery anode, lithium metal has an extremely high energy density, approximately 3860 mAh·g. -1 However, a significant bottleneck exists: lithium metal is prone to severe side reactions at the interface with traditional liquid electrolytes, posing safety risks. Therefore, solid-state batteries are considered a key direction for promoting the safe application of lithium metal batteries. All-solid-state batteries are batteries where ion transfer between the positive and negative electrodes is entirely achieved through a solid electrolyte. Compared to liquid electrolytes (commonly known as electrolyte solutions), solid electrolytes are less flammable and have higher thermal stability, effectively avoiding problems such as electrolyte leakage and combustion, thus significantly improving battery safety.
[0003] One of the core challenges in the practical application of solid-state batteries lies in the regulation and optimization of the solid-solid interface, encompassing aspects such as interfacial compatibility, electrode stability, and mechanical strength. This is also a crucial issue affecting the development of solid-state electrolytes. Solid-state electrolytes include inorganic solid-state electrolytes and organic polymer electrolytes. Among them, polymer electrolytes exhibit high industrialization value and potential due to their advantages such as flexible chains, ease of processing, and low production costs. However, while the flexibility of single organic polymer electrolyte chains provides good interfacial contact, it also results in insufficient mechanical strength, making it difficult to effectively suppress the piercing growth of lithium dendrites, thus negatively impacting the long-cycle stability of the battery.
[0004] To improve the mechanical properties of polymer electrolytes, researchers often introduce inorganic fillers to form composite solid electrolytes. Polyethylene oxide (PEO) is one of the most widely studied matrices in solid polymer electrolytes; filler materials are mainly ceramic electrolytes and inert particles. However, in solid composite electrolyte systems, filler particles are often difficult to disperse uniformly and are prone to agglomeration, leading to uneven local current distribution and consequently uneven lithium-ion deposition at the interface. Furthermore, changes in interfacial stress between inorganic particles and the polymer matrix may accelerate the degradation of battery performance. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a solid polymer composite electrolyte, its preparation method and solid battery. When the solid polymer composite electrolyte of the present invention is applied in a battery, it can improve the ionic conductivity while maintaining good mechanical properties and suppressing dendrite growth, thereby facilitating the realization of stable long-cycle battery.
[0006] This invention provides a solid polymer composite electrolyte, comprising a rigid polymer fiber substrate and a composite electrolyte layer formed on the rigid polymer fiber substrate by casting a precursor solution; the rigid polymer fiber substrate is ion-conducting inert, and the precursor solution comprises an electrolyte salt, polyethylene oxide and a Lewis acid, wherein the Lewis acid is an organic copper salt.
[0007] In some preferred embodiments, the rigid polymer fiber of the rigid polymer fiber substrate is one or more of polyimide fiber, aramid fiber, polyetherketone fiber, polysulfone fiber and poly(p-phenylenebenzodioxazole) fiber.
[0008] In some preferred embodiments, the organic copper salt is copper tetraacetonitrile hexafluorophosphate and / or copper tetraacetonitrile tetrafluoroborate.
[0009] In some preferred embodiments, the electrolyte salt is a lithium salt, and the lithium salt is at least one selected from lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate.
[0010] In some preferred embodiments, the molar ratio of the lithium salt to the Lewis acid is 30 to 180:1.
[0011] In some preferred embodiments, the solid polymer composite electrolyte is an electrolyte membrane with a thickness of 100~200μm.
[0012] This invention provides a method for preparing the solid polymer composite electrolyte described above, comprising the following steps:
[0013] Rigid polymer fiber membranes are formed by electrospinning using a rigid polymer spinning solution.
[0014] A precursor solution was prepared by dissolving polyethylene oxide, an electrolyte salt, and a Lewis acid in an organic solvent.
[0015] The precursor solution is poured onto a rigid polymer fiber membrane to form a composite wet membrane. After removing the organic solvent, a solid polymer composite electrolyte is obtained.
[0016] In some preferred embodiments, the precursor solution is prepared in an inert protective atmosphere, wherein the organic solvent is acetonitrile.
[0017] In some preferred embodiments, the composite wet film is first allowed to evaporate naturally for 1-3 hours, and then vacuum dried at 50-60°C to obtain a solid polymer composite electrolyte.
[0018] The present invention provides a solid-state battery, including a solid electrolyte, wherein the solid electrolyte is the solid polymer composite electrolyte described above.
[0019] Compared with existing technologies, this invention provides a high-strength, well-compatible solid polymer composite electrolyte, comprising: a rigid polymer fiber substrate with ion-conducting inertness, and a composite electrolyte layer formed on the substrate by casting a precursor solution; the precursor solution contains an electrolyte salt, polyethylene oxide, and a Lewis acid, wherein the Lewis acid is an organic copper salt. The embodiments of this invention mainly employ a functionalized partitioning strategy to design the electrolyte structure, wherein the randomly distributed polymer fiber skeleton serves as a rigid region, which can suppress lithium dendrite growth, and the Lewis acid improves ionic conductivity by reducing the crystalline regions of the ion transport region through electrostatic interactions. The composite electrolyte exhibits significantly improved overall performance, balancing the challenge of simultaneously achieving good interfacial compatibility and mechanical properties within a battery. Attached Figure Description
[0020] Figure 1 This is a cross-sectional SEM image of the composite polymer electrolyte membrane of Example 1;
[0021] Figure 2 This is an EDS fluorine element mapping diagram of the composite polymer electrolyte membrane of Example 1;
[0022] Figure 3 This is a tensile strength test comparing the addition of Lewis acid to a high-strength polymer film without the addition of high-strength polymer film.
[0023] Figure 4 It is a tensile strength test comparing the addition of a polymer membrane and the addition of Lewis acid before and after the addition of Lewis acid;
[0024] Figure 5 The Fourier transform infrared absorption spectra of the PEO electrolyte membranes in Comparative Examples 1-2 are shown.
[0025] Figure 6 These are the long-cycle test results of the composite polymer electrolyte symmetric battery in Example 1;
[0026] Figure 7 This is a SEM image of the lithium electrode cross-section after 4000 hours of long-cycle operation of the composite polymer electrolyte symmetric battery in Example 1.
[0027] Figure 8 The results are from a long-cycle test at 60°C and 0.5C on a Li / / LFP full cell assembled with the composite polymer electrolyte of Example 1. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention.
[0029] Compared to the solid-liquid interface of liquid electrolyte systems, improvements in solid-solid interface compatibility, electrode stability, and mechanical strength are crucial factors driving the development of solid-state electrolytes. As a structural component for battery ion conduction, solid-state electrolytes need to be flexible to ensure close contact with the electrodes, fill the voids in the electrode active materials, and guarantee charge transfer at the interface; they also need flexible chain segments to ensure efficient ion transfer within the bulk phase.
[0030] In addition, during the cycling of lithium metal batteries, uneven deposition of lithium metal on the electrode surface and the tip discharge effect lead to the formation of lithium dendrites, which gradually grow as the battery is continuously charged and discharged, eventually piercing the electrolyte and causing safety problems such as battery short circuits. Polymer electrolytes also need to have sufficient mechanical strength to resist the dendrite growth and piercing process.
[0031] For single organic polymer electrolytes, a lower glass transition temperature implies higher molecular chain mobility and a softer polymer surface. Therefore, there is a trade-off between good ionic conductivity and high mechanical properties. Consequently, balancing mechanical strength and interfacial compatibility has become an important research topic for organic polymer electrolytes.
[0032] While introducing fillers is beneficial for long-term battery cycling, addressing the issues of uneven filler dispersion and the provision of dendrite growth pathways by regular crystalline structures, and achieving effective suppression of lithium dendrites, has become a highly promising area for improvement. Introducing rigid polymer fibers could be considered, but increasing the ion transport efficiency in the flexible phase region becomes crucial in balancing strength and ion conductivity.
[0033] Ion conductivity is closely related to the solvation structure and transport mechanism between ions. In polymer electrolytes, electronegative functional groups coordinate with lithium ions and, under the influence of an electric field, achieve directional ion migration through segmental movement and interchain ion transitions. This transport mechanism dictates that polymer electrolytes require a lower glass transition temperature and more amorphous regions. Therefore, suppressing polymer crystallinity, decoupling interchain molecular interactions, and designing solvation structures are effective strategies to improve polymer conductivity. Currently, introducing Lewis acids and utilizing their hydrogen bonding to disrupt the crystalline regions of the electrolyte and increase the amorphous regions for ion conduction can improve the performance of polymer electrolytes to some extent. Lewis acids (LA) refer to electron acceptors, i.e., compounds with empty orbitals that can accept electron pairs, and can also be considered as centers for forming coordinate bonds.
[0034] However, existing strategies mainly focus on improving the ion conductivity of single-phase electrolytes, with limited improvement on the stability of lithium metal electrodes. Furthermore, while the introduction of inorganic fillers improves the mechanical properties of the material, inorganic fillers have poor compatibility with organic electrolytes, are prone to agglomeration, and grain boundaries can easily become pathways for lithium dendrite growth.
[0035] This invention provides a solid polymer composite electrolyte, comprising a rigid polymer fiber substrate and a composite electrolyte layer formed on the rigid polymer fiber substrate by casting a precursor solution; the rigid polymer fiber substrate is ion-inert, and the precursor solution comprises an electrolyte salt, polyethylene oxide and a Lewis acid, wherein the Lewis acid is an organic copper salt.
[0036] The solid polymer composite electrolyte provided by this invention has high strength and good interfacial compatibility. It can solve the contradiction between the flexibility improvement brought about by the increase in ionic conductivity and the mechanical properties required to prevent dendrite growth that are difficult to balance in a single-phase electrolyte, and overcome the limitations of poor compatibility of organic and inorganic composite materials leading to the agglomeration of inorganic fillers.
[0037] The solid polymer composite electrolyte of this invention comprises a rigid polymer fiber substrate with ion-conducting inertness. This invention uses a low dielectric constant (typically less than 2.8), high strength, and stable inert polymer fiber membrane material as the polymer backbone substrate to support and enhance the mechanical strength of the polymer electrolyte, effectively resisting lithium dendrite penetration. Preferably, the rigid polymer fiber of the rigid polymer fiber substrate is one or more of polyimide fibers, aramid fibers, polyetherketone fibers, polysulfone fibers, and poly(p-phenylenebenzodioxazole) fibers, further comprising polyimide fibers (PI fibers).
[0038] Polyimide (PI) is a class of high-performance organic polymer materials containing imide ring (-CO-NR-CO-) structural units in its main chain. It is typically prepared by the polycondensation reaction of aromatic dianhydrides and diamine monomers. Industrially, polyimides are often synthesized using a two-step method (polyamic acid method) or a one-step method. Polyimides possess excellent physical properties, and their macroscopic characteristics are related to the rigid imide rings and aromatic backbone in their molecular structure. Different structural types of polyimides exhibit certain differences in rigidity and flexibility. Some embodiments of this invention may use p-phenylenediamine (PPD), benzimidazole (BIA), and 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA) as the polyimide polymer substrate formed through a two-step method.
[0039] The aramid fibers include meta-aramid (PMIA) and para-aramid fibers; polyetherketone fibers such as polyetheretherketone (PEEK) and polyaryletherketone (PAEK) fibers; polysulfone fibers such as polysulfone (PSF), polyethersulfone (PES), and polysulfonamide (PSA) fibers; and poly(p-phenylenebenzodioxazole) fibers, abbreviated as PBO fibers.
[0040] Furthermore, in embodiments of the present invention, the rigid polymer fiber substrate can be formed by electrospinning, with the polymer fiber filaments uniformly and randomly arranged and aggregated into a supporting membrane morphology. Electrospinning is a processing technology that uses a high-voltage electrostatic field to prepare polymer solutions or melts into micro / nano-scale fibers, which can be used to manufacture micro / nano-fiber membranes. Its basic apparatus includes a high-voltage power supply, a spinneret, and a collection device. Primarily, the electric field force causes charged droplets of the spinning solution to be ejected into a jet, which is then solidified into fibers in the collection device. The diameter and morphology of the fibers can be controlled by adjusting the electrospinning process parameters.
[0041] Furthermore, this embodiment of the invention employs a specific precursor to form a composite electrolyte layer on a rigid polymer fiber substrate using a solution casting process. The precursor solution comprises an electrolyte salt (typically a lithium salt), polyethylene oxide (PEO), and a Lewis acid-organic copper salt; it forms a PEO-based electrolyte with uniformly distributed Cu ions, which uniformly permeates between the substrate polymer membrane and can encapsulate the rigid fiber filaments. The Lewis acid-organic copper salt can disrupt the crystalline regions through electrostatic interactions, improving the ion conductivity of the ion-conducting phase while maintaining good mechanical strength.
[0042] In specific embodiments of the present invention, the morphology of the composite electrolyte can be displayed by scanning electron microscopy (SEM). SEM is a testing technique that uses a focused electron beam to scan the sample surface to observe the morphology, composition, and structure of the sample surface. The introduction and distribution of Lewis acids can also be displayed by energy-dispersive X-ray spectroscopy (EDS). EDS is used to perform elemental analysis of the sample by detecting the characteristic X-rays emitted by the sample under electron beam bombardment.
[0043] Preferably, the organic copper salt described in the embodiments of the present invention is copper tetraacetonitrile hexafluorophosphate and / or copper tetraacetonitrile tetrafluoroborate, and more preferably copper tetraacetonitrile hexafluorophosphate ([(CH3CN)4Cu]PF6), which can be more uniformly and efficiently dispersed in the PEO-based system.
[0044] The lithium salt described in the embodiments of the present invention may be at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate, and may further be LiTFSI. In the embodiments of the present invention, the molar ratio of the lithium salt to the Lewis acid is preferably 30-180:1, for example, 30:1, 40:1, 50:1, 60:1, 100:1, 120:1, 150:1, or 180:1. Excessive Lewis acid content will lead to a significant decrease in the mechanical strength of the polymer.
[0045] In a specific embodiment of the present invention, the solid polymer composite electrolyte is an electrolyte membrane with a thickness of 100~200μm; its tensile strength can be 8~10MPa.
[0046] This invention provides a method for preparing the solid polymer composite electrolyte described above, comprising the following steps:
[0047] Rigid polymer fiber membranes are formed by electrospinning using a rigid polymer spinning solution.
[0048] A precursor solution was prepared by dissolving polyethylene oxide, an electrolyte salt, and a Lewis acid in an organic solvent.
[0049] The precursor solution is poured onto a rigid polymer fiber membrane to form a composite wet membrane. After removing the organic solvent, a solid polymer composite electrolyte is obtained.
[0050] This invention does not impose special restrictions on the process for forming rigid polymer fiber membranes. Taking the two-step synthesis of polyimide fiber membranes—electrospinning—as an example, the embodiments of this invention first prepare a polyamide spinning solution. Using N,N-dimethylacetamide (DMAC) as a solvent, diamine and aromatic dianhydride monomers are reacted to obtain a clear, bright brown liquid, which is the spinning solution. A certain volume of the spinning solution is loaded into a syringe syringe and electrospinned to obtain a polyamide electrospun membrane. After dehydration and imidization, a polyimide fiber membrane is formed. The room temperature viscosity range of the spinning solution can be 700-4200 mPa·s, which is used for polyamic acid spinning. In the electrospinning process, the voltage is 1~40 kV, the roller speed is 1000 r / min, and the feed rate is 1 mL / h. Subsequently, imidization can be carried out by heating to 310~320℃.
[0051] In a specific embodiment of the present invention, polyethylene oxide (PEO) and lithium salt are first dissolved in an organic solvent such as acetonitrile, and then an organic copper salt is added according to a molar ratio. The mixture is stirred thoroughly to obtain a precursor solution; the precursor solution can be denoted as PEO-Cu. + The electrolyte solution, or precursor solution, is used, and the above operations are preferably performed in an inert protective atmosphere. The molar ratio of the lithium salt to the Lewis acid organic copper salt is preferably 30~180:1, as described above.
[0052] In this embodiment of the invention, the polyimide fiber membrane can be cut to a suitable size, placed in a polytetrafluoroethylene container, and the precursor liquid can be poured onto the polymer fiber substrate using a solution casting method. Preferably, the obtained composite wet membrane is allowed to evaporate naturally for 1-3 hours, and then vacuum dried at 50-60°C to obtain a composite polymer electrolyte membrane, which is the solid polymer composite electrolyte.
[0053] This invention provides a solid-state battery, including a solid-state electrolyte, which is the solid polymer composite electrolyte described above. Based on the functionalized partitioning of this solid-state electrolyte and its synergistic effect of Lewis acid complexation, embodiments of this invention can achieve good application of long-cycle stable PEO-based all-solid-state battery products.
[0054] The embodiments of the present invention do not have any special restrictions on whether the negative electrode and the positive electrode of the battery are the same; the negative electrode can be a lithium sheet and the positive electrode can be lithium iron phosphate, and the full battery is assembled according to conventional operation.
[0055] The functionalized partitioning proposed in this invention involves modifying components with different properties in the composite material according to their respective engineering objectives, resulting in relatively clear boundaries and functional allocation between components. This invention primarily combines a functionalized partitioning strategy, introducing an ion-inert polymer fiber substrate as a rigid region, and introducing a Lewis acid to disrupt the crystalline region of the flexible electrolyte, thus enhancing ion conductivity while preserving mechanical strength. This invention uses an organic copper salt as the Lewis acid in the composite system, which exhibits better dispersibility within the organic phase.
[0056] Cyclic performance testing showed that the solid-state battery described in some embodiments of the present invention can stably cycle 700 times with a capacity retention rate of 93%.
[0057] To better understand the technical content of this application, specific embodiments are provided below for further explanation. All raw materials involved are commercially available conventional products and are not subject to special restrictions; among them, the molecular weight of PEO is 600,000.
[0058] Example 1
[0059] (1) The preparation of polyimide fiber membrane includes: preparing polyamide spinning solution and electrospinning; the specific operation is as follows.
[0060] Preparation of polyamide spinning solution: DMAC was added to a three-necked flask and stirred. Then 11.21 g BIA (benzimidazole), 5.41 g PPD (p-phenylenediamine), and 29.42 g BPDA (3,3',4,4'-biphenyltetracarboxylic anhydride) were added to the three-necked flask. Nitrogen gas was introduced for protection, and the mixture was stirred for 8 hours to obtain a clear, bright brown liquid.
[0061] Electrospinning: Take 5 mL of the above polyamide spinning solution and load it into a syringe. Set the absolute values of both positive and negative voltages to 20 kV, the roller speed to 1000 r / min, and the feed rate to 1 mL / h. Collect the solution. Remove the polyamide electrospun membrane and dry it in a forced-air oven at 80℃. Then, perform gradient heating to dehydrate and imidize the polyamide fiber membrane, forming a polyimide fiber membrane substrate.
[0062] (2) Preparation of polymer composite electrolyte
[0063] Preparation of precursor solution: according to EO:Li + PEO and LiTFSI were dissolved in acetonitrile (0.8 g PEO, 0.27 g lithium salt) at a molar ratio of 15:1, and stirred thoroughly in an argon glove box for 6 hours to obtain precursor solution 1. The precursor solution 1 was then processed according to the Li... + Cu + =60:1, add [(CH3CN)4Cu]PF6, and stir thoroughly to obtain precursor solution 2.
[0064] Preparation of composite electrolyte membrane: The polyimide fiber membrane obtained in step (1) was cut to a suitable size and placed in a polytetrafluoroethylene container. The precursor solution 2 was poured onto the polymer substrate using a solution casting method. The resulting composite wet membrane was allowed to evaporate naturally for 2 h, and then vacuum dried at 60 °C for 10 h to obtain the composite polymer electrolyte membrane, denoted as PI@PEO-Cu. + .
[0065] Comparative Example 1
[0066] Preparation of non-composite electrolyte membrane:
[0067] Precursor liquid 1 was poured into a polytetrafluoroethylene mold and allowed to evaporate naturally for 2 hours. Then it was vacuum dried at 60°C for 10 hours to obtain uncomposite PEO-based electrolyte (PEO alone).
[0068] Comparative Example 2
[0069] Without PI membrane support, and with the addition of Lewis acids, the electrolyte can be denoted as PEO-Cu. + .
[0070] Comparative Example 3
[0071] PI@PEO preparation: A PI membrane was used as a support, but Lewis acid was not used; the operation was the same as in Example 1, and the main purpose was to explore the effect of the PI membrane itself on the electrolyte performance.
[0072] Figure 1 The image shown is a cross-sectional SEM image of the composite polymer electrolyte membrane of Example 1. It can be seen that the PEO-based electrolyte is uniformly permeated between the polymer membranes, and the thickness of the electrolyte membrane after composite is about 150µm. Figure 2 The results show that the fluorine carried by the Lewis acid in the electrolyte membrane is relatively evenly distributed throughout the system.
[0073] like Figure 3 , Figure 4 As shown, compared to 0.63 Pa for the PEO phase alone, the PEO-Cu phase after adding Lewis acid... + The mechanical strength reached 2.19 MPa. In this invention, the rigid polymer fiber membrane significantly improved the mechanical strength of the electrolyte membrane, PI@PEO-Cu + The tensile strength reached 8.57 MPa, and the introduction of Lewis acid and electrostatic interaction between the PEO molecular chains also improved the mechanical strength of the composite electrolyte membrane to some extent (the tensile strength of PI@PEO was 8.12 MPa, lower than that of PI@PEO-Cu). + (tensile strength).
[0074] Subsequently, the characteristic peaks of the stretching vibration of the ether oxygen bond were observed using infrared spectroscopy; such as Figure 5 As shown, the changes after adding Lewis acids to PEO revealed that the interaction between Lewis acids and the lone pair electrons of the ether oxygen bond reduced the vibrational frequency of the -COC- bond, and the characteristic peak position redshifted.
[0075] Example 2
[0076] PEO-Cu was obtained by repeating the process in Example 1 above. + The difference in the steps for electrolyte solutions lies in the ratio of lithium salt to Lewis acid: Li + Cu + A precursor solution with a ratio of 30:1 is denoted as precursor solution 3.
[0077] The precursor liquid 3 was poured onto the polymer substrate using a solution casting method; the resulting composite wet membrane was allowed to evaporate naturally for 2 hours, and then vacuum dried at 60°C for 10 hours to obtain the composite polymer electrolyte membrane.
[0078] Example 3
[0079] PEO-Cu was obtained by repeating the process in Example 1 above. + The difference in the electrolyte solution steps is that the proportion of Li in the precursor solution is replaced. + Cu+ =15:1, denoted as precursor solution 4.
[0080] The precursor liquid 4 was poured onto the polymer substrate using a solution casting method; the resulting composite wet film was allowed to evaporate naturally for 2 hours, and then vacuum dried at 60°C for 10 hours to obtain a composite polymer electrolyte membrane.
[0081] Excessive Lewis acid content can lead to a significant decrease in the mechanical strength of the polymer. In Examples 1-3, the ratio of PEO ether oxygen group to lithium salt was 15:1, and the molar ratio of lithium salt to Lewis acid was 30:1, which was the ratio with the best overall performance after screening.
[0082] Example 4
[0083] To investigate the stability of the composite electrolyte membrane for lithium anodes and its interfacial lithium-ion deposition performance, PI@PEO-Cu was used. + PEO and PPO were assembled into symmetrical cells, and tested at 60℃ and a current density of 0.1 mA·cm⁻¹. -2 Perform long-cycle testing under these conditions. Figure 6 As shown, the polymer electrolyte with functionalized partitions exhibits lower interfacial polarization and can cycle stably for 4000 hours; while the pure PEO electrolyte shows a short circuit after 225 hours of cycling. This indicates that the composite modification of this invention results in better interfacial compatibility and effectively alleviates the growth of lithium dendrites.
[0084] To further verify the more uniform lithium-ion deposition, scanning electron microscopy was performed on the lithium electrode interface after 4000 hours of cycling. Results are shown below. Figure 7 As can be seen, its surface is relatively flat, without sharp protrusions formed by lithium dendrite growth. This means that the Lewis acid strategy reduces crystallinity, guiding lithium ions to be inserted and extracted more evenly on the electrode surface. The rigid polymer fiber substrate also effectively protects the battery from lithium dendrite growth and puncture.
[0085] The negative electrode is a lithium sheet, and the positive electrode is loaded with 1 mg·cm⁻¹. -2 Lithium iron phosphate (LFP) cells were assembled into full cells according to Example 1 and Comparative Example 1, and subjected to long-term cycle testing at 0.5C. Results are shown below. Figure 8 Among them, the pure-phase PEO electrolyte showed fluctuations in coulombic efficiency and gradually failed after 250 cycles; while PI@PEO-Cu + The full battery can stably cycle for 700 cycles with a capacity retention of 93% and a Kunlun efficiency consistently above 99.7%. This demonstrates that the polymer electrolyte with its functionalized partitioned design in this embodiment of the invention effectively improves the long-cycle performance of the full battery.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A solid polymer composite electrolyte, characterized in that, It includes a rigid polymer fiber substrate and a composite electrolyte layer formed on the rigid polymer fiber substrate by casting a precursor solution; the rigid polymer fiber substrate is ionically inert, and the precursor solution contains an electrolyte salt, polyethylene oxide and a Lewis acid, wherein the Lewis acid is an organic copper salt.
2. The solid polymer composite electrolyte according to claim 1, characterized in that, The rigid polymer fiber of the rigid polymer fiber substrate is one or more of polyimide fiber, aramid fiber, polyetherketone fiber, polysulfone fiber and poly(p-phenylenebenzodioxazole) fiber.
3. The solid polymer composite electrolyte according to claim 1, characterized in that, The organic copper salt is copper hexafluorophosphate tetraacetonitrile and / or copper tetrafluoroborate tetraacetonitrile.
4. The solid polymer composite electrolyte according to claim 1, characterized in that, The electrolyte salt is a lithium salt, and the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate.
5. The solid polymer composite electrolyte according to claim 4, characterized in that, The molar ratio of the lithium salt to the Lewis acid is 30~180:
1.
6. The solid polymer composite electrolyte according to any one of claims 1-5, characterized in that, The solid polymer composite electrolyte is an electrolyte membrane with a thickness of 100~200μm.
7. A method for preparing a solid polymer composite electrolyte as described in any one of claims 1-6, characterized in that, Includes the following steps: Rigid polymer fiber membranes are formed by electrospinning using a rigid polymer spinning solution. A precursor solution was prepared by dissolving polyethylene oxide, an electrolyte salt, and a Lewis acid in an organic solvent. The precursor solution is poured onto a rigid polymer fiber membrane to form a composite wet membrane. After removing the organic solvent, a solid polymer composite electrolyte is obtained.
8. The preparation method according to claim 7, characterized in that, The precursor solution was prepared in an inert protective atmosphere, and the organic solvent therein was acetonitrile.
9. The preparation method according to claim 7, characterized in that, The composite wet film is first allowed to evaporate naturally for 1-3 hours, and then dried under vacuum at 50-60°C to obtain a solid polymer composite electrolyte.
10. A solid-state battery, comprising a solid electrolyte, characterized in that, The solid electrolyte is the solid polymer composite electrolyte according to any one of claims 1-6.
